"Expect the unexpected": New perspectives on uncertainty management and value logics in event management. Issue 1 (16th March 2015) - Ellert, Guido; Schafmeister, Guido; Wawrzinek, David; Gassner, Heike
Abstract : Purpose: – The purpose of this paper is to analyse event management by using three value creation logics, value chain, value network and value shop. In event management, value is generated through intermediation where the dominant creation logic is a value network. However, the complexity of events and danger of unexpected problems is increasing, which, in the worst case, leads to event failure. This fact makes it necessary to change the general attitude towards this topic from risk management to uncertainty management and use the value shop in order to solve problems efficiently. Design/methodology/approach: – This paper is based on the methodology of phenomenological hermeneutics which analyzes the object of study by interpreting the facticity and provides basics to generate a conceptual model. Findings: – The dominant value creation logic must be changed to prevent the value network from failure in generating value, since only the value shop provides high quality problem solving. Trust not only in planning but also in the own problem-solving competence and available tools is a major part of the value shop. As a practical example of high quality problem solving, the performance of high reliability organisations can be used by event managers. Research limitations/implications: – Using these hermeneutical gained logic, additional empirical research projects in event management, leadership and problem-solving competence of top managers, are promptly intended. Additionally, studies concerning competences and structures of the uncertainty management team have to be determined and developed as well as education and coaching has to be generated in order to achieve best results in problem solving. Practical implications: – Practical implications of this paper are: considering the value shop as the dominant value creation logic in uncertainty management; establishing a specially trained Complex Problem-Solving Team; and considering trust to be an essential element of the value shop. Social implications: – The basic job requirements a successful value net (event-) manager has to provide in such a complex system are: acting as integrator, mediator and problem solver simultaneously. Additionally event managers need to be trained to rethink the value creation logic and use the value shop within the value net to stay flexible and work successfully during their events. Originality/value: – Derived from this new perspective the necessity of enhancing the implemented value creation logic according to uncertainties allows event managers to solve unexpected problems faster and more efficiently.